Economic and fast electro-flotation extraction of heavy metals from wastewater. Issue 25 (10th November 2022) - Ali, Imran; Tatiana, Kon'kova; Zaw Htay, Than; Thu Aung, Hein; Ekaterina, Mishenko; Nahid Siddiqui, Mohammad; Almalki, Abdulraheem S. A.; Alhadhrami, A.; alsubaie, Abdullah; Hameed, Ahmed M.; Alharbi, Ahmed
ABSTRACT: Fast electroflotation extraction of heavy metals from wastewater is described. The results of experimental investigations of the extraction of iron, aluminium and chromium hydroxides from aqueous solutions in the presence of surfactants of various natures and ions of calcium by electroflotation are presented. It was found that the presence of Ca 2+ in the solution at a concentration of 0.5 g/L reduced the degree of electroflotation extraction of Al(OH)3, Fe(OH)3, Cr(OH)3 regardless of the nature of the electrolyte. The addition of surfactants in the system in the presence of Ca 2+ increased the amount of extraction of the dispersed phase. The greatest effect is achieved with the help of anionic surfactant sodium dodecyl sulphate, while the degree of extraction reached 98%. The high efficiency of the process of electroflotation extraction of the dispersed phase was due to the hydrophobization of the particle surface owing to the adsorption of surfactants on the surface of hydroxides. The recent method is useful to treat wastewater contaminated with aluminium, iron and chromium metal ions. The reason is that this method is very fast working within 20 min; Moreover, pH 7.0 working made this method ideal for utilisation in natural water treatment economically. GRAPHICAL ABSTRACT: UF0001